The Effects of Market Structure Characteristics on Competitive Reaction Intensity: A Longitudinal Analysis - REDDY, Srinivas K. (Institutional Knowledge at Singapore Management University, 1991)
This study explores the effects of market structure characteristics and exogenous market interventions on competitive reaction intensity over time. It is found that moderate growth rate and moderate concentration induce greater competitive reactions. The effect of the exogenous intervention in the industry studied appears to have a dampening impact on competitive responses. Our research inquiry addresses some issues raised on competition, in general, by Weitz (1985) and specifically on competitive responses by Robinson (1988) and Gatignon, Anderson, and Helsen (1989).